The Effectiveness and Potential Improvements of a Voluntary Code of Conduct for Whale-Watching in Iceland - Renée Blankenstein 1991- (2021)
Iceland’s whale-watching industry has seen dramatic growth in recent years. However, since no legislation currently exists to manage these operations, questions have arisen regarding the industry’s potential impacts on cetaceans and thus its sustainability. In 2015, the Icelandic Whale Watching Association (IceWhale) introduced a voluntary code of conduct containing guidelines for how whale-watching vessels should behave around cetaceans. Being fairly new, the code of conduct’s effectiveness has not been researched extensively. This study therefore aims to assess the effectiveness of the voluntary code of conduct for whale-watching in Iceland and suggest potential improvements. Fifteen semi-structured interviews were conducted with stakeholders who are/were involved in the code of conduct’s development or management, use/have used it in practice, have knowledge about potential whale-watching impacts on cetaceans, or a combination thereof. Results found that the voluntary aspect of the code of conduct likely reduces its effectiveness and that operator compliance seems to depend on many factors, such as knowledge of crew and pressure caused by high passenger expectations. Furthermore, potential impacts of underwater noise and vessel crowding, among others, seem to be addressed insufficiently at present. Recommendations include a move towards adaptive management with a focus on increased monitoring and enforcement, and education of staff and passengers. Furthermore, certain changes regarding the code of conduct’s wording and contents are suggested. Implementation of the proposed recommendations may increase the sustainability of Iceland’s whale-watching industry by ensuring the protection of the cetaceans involved as well as the ecosystem services they provide.